Controle químico de manchas foliares em diferentes cultivares de soja - Araújo Júnior, Ivan Pedro de (2021)
ARAÚJO JÚNIOR, I. P. Chemical control of leaf spots in different soybean cultivars. 2021. 61f. Dissertation (Master in Agronomy) – Federal University of Uberlândia, Uberlândia, 2021. Target leaf spot (Corynespora cassiicola) and cercospora leaf blight – CFC in Portuguese abbreviation (Cercospora spp.) are among the main leaf diseases of economic importance in soybean crop. The damage may vary according to the characteristic of the cultivar, disease severity, stage of occurrence in the crop cycle, climatic conditions and effectiveness of chemical control. Therefore, the objective of this work was to evaluate the interaction between fungicide programs, amount of applications and time of first application in different soybean cultivars, in order to control leaf spots, whose variable were disease severity (%), control efficacy (%), productivity (kg.ha-1) and thousand grain weight (g) responses. The experiment was conducted at Proteplan research station in Sorriso, Mato Grosso, Brazil, from October 2019 to March 2020. The treatments consisted of fungicide programs, with the combination of site-specific and multisite commercial products at different times of application, totaling six programs and the witness. The treatments were: (1) check; (2) fluxapyroxad + pyraclostrobin + mancozeb (35 days after emergency – DAE); (3) fluxapyroxad + pyraclostrobin + mancozeb (35 DAE) and prothioconazole + trifloxystrobin + bixafen (50 DAE); (4) fluxapyroxade + pyraclostrobin + mancozeb (35 DAE), prothioconazol + trifloxystrobin + bixafen (50 DAE) and difenoconazol + cyproconazol + chlorothalonil (75 DAE); (5) fluxapyroxad + pyraclostrobin + mancozeb (50 DAE); (6) fluxapyroxad + pyraclostrobin + mancozeb (50 DAE) and prothioconazole + trifloxystrobin + bixafen (75 DAE); (7) fluxapyroxad + pyraclostrobin + mancozeb (50 DAE), prothioconazol + trifloxystrobin + bixafen (75 DAE) and difenoconazol + cyproconazol + chlorothalonil (90 DAE) – the cultivars BMX Fecha IPRO, TMG 2181 IPRO and Msoy 8372 IPRO were used. The final target spot severity evaluated in the plots without fungicides ranged between 1.3% and 45.0% and, for CFC, between 14.3% and 44.5%, which allowed the classification of cultivars in relation to resistance to these diseases. In the cultivar with genetic resistance to C. cassiicola (BMX Flecha IPRO) and susceptibility to CFC, no correlation was observed between time and number of applications, with similar productivity between treatments. Then, in the cultivar susceptible to C. cassiicola (TMG 2181 IPRO), there was a significant response in target spot control for treatments with two and three applications (35 DAE) and in yield for the treatment with three applications (35 DAE). And in cultivar Msoy 8372 IPRO (susceptible to CFC and with moderate resistance to the target spot), there was a significant response in leaf spot control for treatments with two (35 DAE) and three applications (35 DAE and 50 DAE) and in productivity for treatments with two and three applications (35 DAE). The percentage of productivity reduction due to diseases ranged from 7.4% (BMX Flecha IPRO) to 24.1% (TMG 2181 IPRO), and the values of PMG (g) varied as a function of fungicide management in BMX Flecha IPRO and TMG 2181 IPRO. In the contrast between application times, higher yields were found in the programs started at 35 DAE (Msoy 8372 IPRO and TMG 2181 IPRO), which demonstrates that it is an effective strategy for the preventive control of leaf spots, especially in susceptible plants.